Development of crisis management competencies: factors dominating it. a case study of local authorities in Malaysia - Muhammad, Norlina; Ismail, Ismi Arif; Arshad, Mohd Mursyid; Md Rami, Ahmad Aizuddin (Human Resource Management Academic Research Society, 2022)
Performance improvement in an organisation can be achieved if all competency elements can be strengthened, employees perform their roles efficiently, and services meet the expectations of the management and customers. The competency development process requires continuous supervision and evaluation in order to produce an effective and integrated management system. The research used a qualitative method, in which eight informants participated in this study to discuss the comprehensive development and factors dominating the process. The themes of the study are derived based on participatory observations, document analysis, and interview sessions that have been conducted. The discussion topic is focused on the components that influence the development of crisis management competencies according to their perspectives. The three themes are 1) Enhancement of the transparency of governance and integrity in organisational human resources, 2) Empowerment of organisational learning to drive organisational excellence, and 3) Strengthening the efficiency of organisational governance. Integrity governance with high expertise requires continuous training and development to increase the knowledge, skills, and abilities of employees from time to time. It also assists in enhancing the talents and expertise of employees in related fields as well as improving self-confidence and personality to achieve the objectives of the transparency of governance.